Functional Gene Analysis Reveals Cell Cycle Changes and Inflammation in Endothelial Cells Irradiated with a Single X-ray Dose - Baselet, Bjorn; Belmans, Niels; Coninx, Emma; Lowe, Donna; Janssen, Ann; Michaux, Arlette; Tabury, Kevin; Raj, Kenneth; Quintens, Roel; Benotmane, Mohammed A.; Baatout, Sarah; Sonveaux, Pierre; et al. (Frontiers in Pharmacology, 2017)
Background and Purpose: Epidemiological data suggests an excess risk of cardiovascular disease (CVD) at low doses (0.05 and 0.1 Gy) of ionizing radiation (IR). Furthermore, the underlying biological and molecular mechanisms of radiation-induced CVD are still unclear. Because damage to the endothelium could be critical in IR-related CVD, this study aimed to identify the effects of radiation on immortalized endothelial cells in the context of atherosclerosis. Material and Methods: Microarrays and RT-qPCR were used to compare the response of endothelial cells irradiated with a single X-ray dose (0.05, 0.1, 0.5, 2 Gy) measured after various post-irradiation (repair) times (1 day, 7 days, 14 days). To consolidate and mechanistically support the endothelial cell response to X-ray exposure identified via microarray analysis, DNA repair signaling (γH2AX/TP53BP1-foci quantification), cell cycle progression (BrdU/7AAD flow cytometric analysis), cellular senescence (β-galactosidase assay with CPRG and IGFBP7 quantification) and pro-inflammatory status (IL6 and CCL2) was assessed. Results: Microarray results indicated persistent changes in cell cycle progression and inflammation. Cells underwent G1 arrest in a dose-dependent manner after high doses (0.5 and 2 Gy), which was compensated by increased proliferation after 1 week and almost normalized after 2 weeks. However, at this point irradiated cells showed an increased β-Gal activity and IGFBP7 secretion, indicative of premature senescence. The production of pro-inflammatory cytokines IL6 and CCL2 was increased at early time points. Conclusions: IR induces pro-atherosclerotic processes in endothelial cells in a dose-dependent manner. These findings give an incentive for further research on the shape of the dose-response curve, as we show that even low doses of IR can induce premature endothelial senescence at later time points. Furthermore, our findings on the time- and dose-dependent response regarding differentially expressed genes, cell cycle progression, inflammation and senescence bring novel insights into the underlying molecular mechanisms of the endothelial response to X-ray radiation. This may in turn lead to the development of risk-reducing strategies to prevent IR-induced CVD, such as the use of cell cycle modulators and anti-inflammatory drugs as radioprotectors and/or radiation mitigators.